Ж.Цэвээн Монголын түүх бичлэгт - Түвшин, С. (Historia Mongolarum, 2003)
This article deals with the issue of Jamsarano Tseveen in Mongolian Historiography. Jamsarano Tseveen was an emeretus scholar and statesman at the first half of the XX century. His contribution to the Mongolian studies and legislation development is renowned. The Mongolian historiography could be divided in two parts: the negative part is historiography about 1920-1980s and positive since 1990.